Earthquakes and Water - Wang, Chi-yuen. (Lecture Notes in Earth Sciences, 2009)
The broad spectrum of hydrologic responses to earthquakes offers a better understanding of the earth's hydrologic system at a scale which is otherwise unachievable; it has also allowed field testing of several long-standing hypotheses which may impact on our understanding of some earthquake-induced hazards. The book is based on a graduate course on Earthquake Hydrology at Berkeley jointly offered by the authors in the past few years. It begins with an introduction of the basic materials to form a basis for understanding the chapters which follow. The book provides a comprehensive overview of the field to interested readers and beginning researchers, and a convenient reference to numerous publications currently scattered in various journals.